Ghrelin and Motilin Control Systems in GI Physiology and Therapeutics - Sanger, Gareth J.; Broad, John; Callaghan, Brid; Furness, John B. (Gastrointestinal Pharmacology, 2017)
Ghrelin and motilin are released from gastrointestinal endocrine cells during hunger, to act through G protein-coupled receptors that have closely related amino acid sequences. The actions of ghrelin are more complex than motilin because ghrelin also exists outside the GI tract, it is processed to des-acyl ghrelin which has activity, ghrelin can exist in truncated forms and retain activity, the ghrelin receptor can have constitutive activity and is subject to biased agonism and finally additional ghrelin-like and des-acyl ghrelin receptors are proposed. Both ghrelin and motilin can stimulate gastric emptying, acting via different pathways, perhaps influenced by biased agonism at the receptors, but research is revealing additional pathways of activity. For example, it is becoming apparent that reduction of nausea may be a key therapeutic target for ghrelin receptor agonists and perhaps for compounds that modulate the constitutive activity of the ghrelin receptor. Reduction of nausea may be the mechanism through which gastroparesis symptoms are reduced. Intriguingly, a potential ability of motilin to influence nausea is also becoming apparent. Ghrelin interacts with digestive function through its effects on appetite, and ghrelin antagonists may have a place in treating Prader-Willi syndrome. Unlike motilin, ghrelin receptor agonists also have the potential to treat constipation by acting at the lumbosacral defecation centres. In conclusion, agonists of both ghrelin and motilin receptors hold potential as treatments for specific subsets of digestive system disorders.